High density polyethylene and metal oxides based nanocomposites for high voltage cable application. Issue 11 (21st October 2021) - Islam, Mobasserul; Rahaman, Mostafizur; Aldalbahi, Ali; Paikaray, Bibhudatta; Moharana, Jayakrushna; Mondal, Subhadip; Das, Narayan Ch.; Gupta, Prashant; Giri, Radhashyam
Abstract: The current research aims to study the influence of loading of aluminum oxide (Al2 O3 ) and titanium dioxide (TiO2 ) nanoparticles on the mechanical, electrical, dielectric, thermal and dielectric breakdown strength properties of high density polyethylene (HDPE) specially used for the main insulation in power cables. The HDPE/Al2 O3 and HDPE/TiO2 nanocomposites were prepared by melt blending technique with different ratios of nanoparticles. A modifier was used to reduce the agglomeration of TiO2 and Al2 O3 nanoparticles inside the HDPE matrix. There are improvement in tensile strength (35% and 47.2%), tensile modulus (37.9% and 40.8%), flexural strength (18.8% and 23.1%), flexural modulus (11.2% and 12.4%), impact strength (11.8% and 13.9%), electrical conductivity (10 2 and 10 4 ), dielectric constant (80% and 224%), dielectric breakdown strength (35% and 41%), thermal stability (43°C and 34°C), melting point (5.5°C and 5.9°C), hardness (7.3% and 9.4%), and crystallization temperature (3.3°C and 4.2°C) of HDPE/Al2 O3 and HDPE/TiO2 nanocomposites, respectively, after certain loading of both fillers compared to neat HDPE. The elongation at break and crystallinity were reduced after the addition of both nanofillers within the HDPE matrix. Except thermal stability, the titania based nanocomposites exhibited good performance compared to alumina based nanocomposites. Overall, this substantial improvement in results showed that both composites can be used for high voltage cable application. Abstract : Variation of dielectric breakdown strength against fillers loadings.